Justus Jorgensen interviewed by Hazel de Berg in the Hazel de Berg collection - Jorgensen, Justus, 1893-1975.; De Berg, Hazel, 1913-1984. (1965)
Jorgensen speaks about his childhood; studying under Bernard Hall and McCubbin; teaching for Max Meldrum; his method of working on a painting; his present interests.
Also available online
Timed summary and transcript (16 p.) available.
Keywords: Jorgensen, Justus, -- 1893-1975 -- Interviews; Artists as teachers -- Australia -- Interviews; Painters -- Australia -- Interviews